Casting temperature dependent wear and corrosion behavior of 304 stainless steel reinforced A356 aluminium matrix bimetal composites fabricated by vacuum-assisted melt infiltration casting - Gecu, Ridvan; Karaaslan, Ahmet (ELSEVIER SCIENCE SA, 2020)
This study aims to determine optimum casting temperature to achieve maximum wear and corrosion resistance in 304 stainless steel (SS) reinforced A356 matrix bimetal composites, which have been developed for use where conventional ceramic reinforced metal matrix composites have been used. Vacuum-assisted melt infiltration casting technique was used to manufacture bimetal composites at the various casting temperatures from 630 degrees C to 880 degrees C. The composite samples were subjected to dry sliding ball-on-disc tests using Al2O3 ball and immersion test in 3.5% NaCl solution for 7-21 days. theta (Fe4Al13) and eta (Fe2Al5) phases developed at A356/304 interfaces and thickened with increasing temperature. Abrasion and adhesion as predominant wear mechanisms were observed in worn surface examinations, while pitting and galvanic corrosion occurred in corroded surfaces. The most suitable casting temperature was found to be 730 degrees C, considering the wear and corrosion properties of produced bimetal composites under certain conditions.
Keywords: Bimetal composite; Melt infiltration casting; Wear; Corrosion; Casting temperature; Vacuum assistance; MECHANICAL-PROPERTIES; ELASTIC-MODULUS; STEEL; OXIDATION; HARDNESS; INDENTATION; CARBON; AL2O3; Engineering; Materials Science